Reviewing treatment outcomes of tuberculosis patients at Zagazig Chest Hospital (2008–2012) - Ramadan M. Nafae; Hanan M. Elshahat; Ahmed Mohamed Said; Mona A. Ibrahim (Egyptian Journal of Chest Disease and Tuberculosis, 2017)
Background: Tuberculosis (TB) is one of major critical heath problem worldwide, where drug treatment is fundamental for controlling TB promoting cure of the patient and breaking the chain of transmission when treatment is completely and correctly followed. Aim of the study: Aim of the study is to assess the treatment outcomes of TB patients at Zagazig Chest Hospital and to identify factors associated with poor outcomes in a trial to achieve the national tuberculosis program (NTP) goals. Patients and methods: This is a cohort study that was carried out at Zagazig Chest Hospital which was in part retrospective and prospective in other part. Analysis of data of 290 tuberculous patients was done where 10 cases were excluded. Demographic, socioeconomic data were reported in addition to radiological, bacteriologic histopathological diagnostic data and history of previous treatment of TB and the used anti-tuberculous treatment regimens with application of directly observed therapy short course (DOTS) strategy. Treatment outcomes were assessed for all patients and were classified either as successful or unsuccessful. Results: Successful treatment outcome was reported in 231 (82.5%) TB cases versus 49 (17.5%) cases with unsuccessful treatment. Successful outcome was significantly associated with middle age (16–35 years) (51.5%) (P < .05), well education (78.8%) (P < .001), absence of history of contact with positive TB case (96.1%) (P < .001), mild to moderate advanced X-ray picture (95.5%) (P < .001) and absence of previous history of anti-tuberculous treatment (87.1%) (P < .01). Multivariate logistic regression analysis for risk factors for unsuccessful outcome revealed that illiteracy (P < .001), history of contact to positive TB cases (P < .001) and far advanced chest X-ray of pulmonary TB (P < .001) were considered as significant predictors. Conclusions: A high rate of successful treatment is reported with application of the NTP (2012) guidelines which was associated with middle age of the patients (16–35 years), well education, mild to moderate advanced X-ray picture and absence of either history of contact with positive TB case or previous history of anti-tuberculous treatment(new case). Illiteracy, history of contact to positive TB cases, far advanced chest X-ray of pulmonary TB and previously treated cases on CAT II regimen could be considered as predictors of unsuccessful outcome.